2019
DOI: 10.1109/jeds.2019.2933369
|View full text |Cite
|
Sign up to set email alerts
|

High Performance ${\beta}$ -Ga2O3 Nano-Membrane Field Effect Transistors on a High Thermal Conductivity Diamond Substrate

Abstract: To suppress severe self-heating under high power density, we herein demonstrate top-gate nano-membrane β-gallium oxide (β-Ga 2 O 3) field effect transistors on a high thermal conductivity diamond substrate. The devices exhibit enhanced performance, with a record high maximum drain current of 980 mA/mm for top-gate β-Ga 2 O 3 field effect transistors and 60% less temperature increase from reduced self-heating, compared to the device on a sapphire substrate operating under identical power density. With improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…(7), the performance of materials such as β-Ga 2 O 3 , with high , but with low thermal conductivity, may suffer due to SH. Therefore, an ultra-thin layer of β-Ga 2 O 3 must be placed on top of a high thermal conductivity substrate (e.g., sapphire [11], diamond [37], AlN [38]) for efficient heat spreading. While a lot of improvements are required in the fabrication techniques of β-Ga 2 O 3 FETs to emerge as the high performing power electronics substrate as originally promised, bilayer β-Ga 2 O 3 devices should be compared against , ( ) expression (Eq.…”
Section: Substrate-awarementioning
confidence: 99%
“…(7), the performance of materials such as β-Ga 2 O 3 , with high , but with low thermal conductivity, may suffer due to SH. Therefore, an ultra-thin layer of β-Ga 2 O 3 must be placed on top of a high thermal conductivity substrate (e.g., sapphire [11], diamond [37], AlN [38]) for efficient heat spreading. While a lot of improvements are required in the fabrication techniques of β-Ga 2 O 3 FETs to emerge as the high performing power electronics substrate as originally promised, bilayer β-Ga 2 O 3 devices should be compared against , ( ) expression (Eq.…”
Section: Substrate-awarementioning
confidence: 99%
“…[ 9–12 ] Unfortunately, the poor thermal conductivity of β ‐Ga 2 O 3 is problematic and inquiring into hetero‐substrates with high thermal conductivity, such as a sapphire, diamond, and aluminum nitride. [ 13–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…While the study in growth of large substrates is an on-going topic, researchers have already demonstrated devices made from gallium oxide [19,20,21,22,23,24,25,26,27]. The demonstrated devices point towards promising advantages in gallium oxide over traditional wide band gap semiconductors like SiC and GaN.…”
Section: Introductionmentioning
confidence: 99%
“…It is a well known fact that higher operation temperature in high power devices can lead to significantly lower lifetimes [29,30]. One way researchers have overcome this problem is by exfoliating gallium oxide [26,27,31] or by growing gallium oxide on single crystal diamond(thermal conductivity ∼ 2000 W/mK) substrates [32]. Another approach that has been recently demonstrated is low temperature bonding of single crystal diamond on β-Ga 2 O 3 [33].…”
Section: Introductionmentioning
confidence: 99%